Rapid identification of bacterial select agents using loop-mediated isothermal amplification - Timothy E. Egbo; Candace D. Blancett; Jackie M. Payne; Christopher P. Stefan; Timothy D. Minogue; John H. Sellers; Jeffrey W. Koehler (BMC Infectious Diseases)
Abstract Background Point of need diagnostics provide efficient testing capability for remote or austere locations, decreasing the time to answer by minimizing travel or sample transport requirements. Loop-mediated isothermal amplification (LAMP) is an appealing technology for point-of-need diagnostics due to its rapid analysis time and minimal instrumentation requirements. Methods Here, we designed and optimized nine LAMP assays that are sensitive and specific to targeted bacterial select agents including Bacillus anthracis, Francisella tularensis, Yersinia pestis, and Brucella spp. Evaluation of each assay determined preliminary limit of detection (LOD) with LOD confirmed across 60 replicates (≥ 95% positivity rate). Testing across a robust set of strains of the target agent, common DNA agents, and near-neighbors documented sensitivity and specificity for independent assays. Results Specifically, all assays were 100% specific and sensitive except for Y. pestis Caf1 (90% inclusive across Y. pestis strains). Conclusion Here, we optimized assay turn-around-time, decreasing a standard 60 min traditional polymerase chain reaction (PCR) to 30 min using LAMP with positive results in as little as 5–10 min. Incorporating point of need sample processing and evaluating the potential inhibitory impact of sample matrices such as whole blood and soil would be needed to enable this test system for use on field-forward clinical and environmental sample testing.